Self-Insurance and Self-Protection as Public Goods - Ulrich Schmidt; Julio R. Robledo; Tim Lohse (Kiel University, Department of Economics, 2007)
Many public goods like lighthouses and fire departments do not provide direct utility but act as insurance devices against shipwreck and destruction. They either diminish the size and/or the probability of the loss. We extend the public good model with this insurance aspect and generalize Samuelson?s efficient allocation rule when self-insurance and self-protection expenditures are pure public goods. Some comparative static results with respect to changes in income and risk behavior are derived. We analyze the interaction of private market insurance with the public good level, both for efficient provision and for private provision equilibria. The privately provided levels of self- insurance and self-protection decrease when market insurance is available, which suggests that the state should invest more in preventing not insurable risks like wars. Additionally, the state should focus on self-protection expenditures if those are better observable than private self-protection effort.
Keywords: G22; H41; 330; Self-insurance; self-protection; efficient provision of public goods; private provision of public goods; market insurance; Öffentliches Gut; Allokationseffizienz; Versicherungsökonomik; Brandschutz; Schiffssicherheit; Theorie